Development Platform for Autonomous Driving in Real and Simulated Environments - Allione, Cristian (2021)
Autonomous car driving has gained popularity in recent years both in industrial and academic environments, leading to numerous commercial and research platforms being constructed for development and testing. Moreover, due to advantages at design time and for testing purposes, several simulation environments have been proposed to simulate the complex dynamics and real-world problems the driving algorithms will face. However, most platforms and simulation environments are not suitable in costs and complexity for research groups beginning to work in the area or for educational purposes. In this work we propose a lowcost 3D-printed hardware 1:10 scale car that allows for development and testing of near SAE level 2 driving automation in software-in-the-loop realistic simulations together with real world scenarios. We demonstrate this by running a lane-centering and a simplified version of adaptive cruise control algorithm in a simulated and real highway-inspired track.